Mechanical properties and fire resistance of composite bamboo materials heat-treated with MOS gelling adhesive at different temperatures - Ximing Liu; Hongyun Cao; Jingfan Ma (PLoS ONE, 2026)
Given the flammability and insufficient MPs of natural bamboo, this study uses Magnesium Oxysulfate (MOS)-Gelling Adhesive (MOS-GA) to prepare high-performance composite bamboo, and examines the effects of various temperature treatments on the MPs and fire resistance of MOS-GA composite bamboo. The results showed that MOS-GA had the best MPs after heat treatment at 400°C. After 7 days of curing, the CS of the specimen ranged from 90.02 MPa to 92.37 MPa, and the FS ranged from 9.52 MPa to 9.67 MPa. The MPs at 600°C decreased, the CS dropped to 10.17 MPa-18.24 MPa, and the FS dropped to 2.08 MPa-3.02 MPa. When treated with MOS-GA at 400°C, the composite bamboo material had a maximum along-grain CS of 79.36 MPa, and a TS and FS of 33.45 MPa and 72.12 MPa. The fire resistance limit of the specimen treated at 400°C reached 98 min, the charring depth was 35.2 mm at 100 min, the internal temperature distribution was reasonable, and it showed good thermal insulation performance and structural integrity. Research shows that moderate heat treatment temperature can effectively balance the MPs and fire resistance of MOS-based composite bamboo, providing a theoretical basis for its application in green fire-resistant buildings.